Investigating Translation Equivalence and Strategies in Harry Potter: In The Phoenix New Order - Bayu Andika Prasatyo; Devian Try Gustary; Theresia Mundi Astuti (Jurnal Sinestesia, 2023)
This present article attempts to investigate the non-equivalence problems as described in JK Rowling’s work Harry Potter: In the Phoenix New Order. Besides that, this current article employs the idea of translation equivalences as introduced by Mona Baker. The study utilizes a descriptive qualitative research. The data are taken from words, phrases, sentences, and texts encountered in the Indonesian translation of Harry Potter; In the Phoenix New Order. This article uncovered that the translation of the targeted text contains non-equivalencies at the word, above word, grammatical, textual, and pragmatic levels. To guarantee successful and efficient translation, translators must employ several tactics, including translation equivalence.